A transmission line analogy for the development of equatorial ionospheric bubbles - Bhattacharyya, A.; Burke, William J. (My University, 2000)
The Pedersen conductivity of the conjugate E regions couples to the equatorial F region through geomagnetic field lines and plays an important role in the development of equatorial spread F bubbles. Earlier work has suggested that the coupling between the E and F regions is effected through field-aligned currents (FACs). However, these currents have not yet been explicitly introduced into theoretical models. This paper considers oppositely propagating Alfvén waves which are launched by equatorial F region perturbations as carriers of FACs and transverse polarization currents. A transmission line analogy is drawn, with the E region loads at the two ends and the generator in the equatorial F region. The currents which flow through the E regions depend on the plasma density of the propagation medium in which the transmission line is immersed. We conclude that whereas small angles between the solar terminator and the magnetic meridian favor the growth of equatorial bubbles, an increase in the plasma density of the propagation medium and a higher altitude of the equatorial F layer allow greater relaxation of the restriction imposed by the E region conductivities on the growth of equatorial bubbles.
Keywords: Equatorial ionospheric bubbles; Field-aligned currents; Equatorial F region; Plasma density